Answer this question......
I will not mark your as brainliest answer
Attachments:
![](https://hi-static.z-dn.net/files/d53/6ba5381ba2b7e3c7d43c2565a8607264.jpg)
Answers
Answered by
3
Answer:
cos⁴x-sin⁴x = (cos²x+sin²x)(cos²x-sin²x)
= cos²x-sin²x
= 1-sin²x-sin²x
= 1-2sin²x
option a
Step-by-step explanation:
bruh
Answered by
2
your answer is option a..
I have returned to my home.
are you so much busy??
Similar questions
Computer Science,
7 months ago
Biology,
7 months ago
Hindi,
1 year ago
Science,
1 year ago
Math,
1 year ago